Functional and phylogenetic responses of motile cryptofauna to habitat degradation. Issue 11 (11th September 2022) - Stella, Jessica S.; Wolfe, Kennedy; Roff, George; Rogers, Alice; Priest, Mark; Golbuu, Yimnang; Mumby, Peter J.
Abstract: Biodiversity of terrestrial and marine ecosystems, including coral reefs, is dominated by small, often cryptic, invertebrate taxa that play important roles in ecosystem structure and functioning. While cryptofauna community structure is determined by strong small‐scale microhabitat associations, the extent to which ecological and environmental factors shape these communities are largely unknown, as is the relative importance of particular microhabitats in supporting reef trophodynamics from the bottom up. The goal of this study was to address these knowledge gaps, provided coral reefs are increasingly exposed to multiple disturbances and environmental gradients that influence habitat complexity, condition and ecosystem functioning. We compared the density, biomass, size range, phylogenetic diversity and functional roles of motile cryptofauna in Palau, Western Micronesia, among four coral‐derived microhabitats representing various states of degradation (live coral [ Acropora and Pocillopora ], dead coral and coral rubble) from reefs along a gradient of effluent exposure. In total, 122 families across ten phyla were identified, dominated by the Arthropoda (Crustacea) and Mollusca. Cryptofauna biomass was greatest in live Pocillopora, while coral rubble contained the greatest density and diversity. Size ranges were broader in live corals than both dead coral and rubble. From a bottom‐up perspective, effluent exposure had mixed effects on cryptic communities including a decline in total biomass in rubble. From a top‐down perspective, cryptofauna were generally unaffected by predator biomass. Our data show that, as coral reef ecosystems continue to decline in response to more frequent and severe disturbances, habitats other than live coral may become increasingly important in supporting coral reef biodiversity and food webs. Abstract : Uncovering the hidden biodiversity of coral reefs. Divers mostly see corals and fishes, but these authors have found increased numbers and diversity of tiny animals hidden in dead coral and rubble. Such animals are overlooked, but may help support food webs and functioning as the living coral structure degrades.